2013
DOI: 10.1017/s1355617712001397
|View full text |Cite
|
Sign up to set email alerts
|

Working Memory and Intelligence Are Associated with Victoria Symptom Validity Test Hard Item Performance in Patients With Intractable Epilepsy

Abstract: Loring et al. (Journal of clinical and experimental neuropsychology, 2005:27;610–617) observed relationships between VSVT hard item performance and IQ and memory indices in epilepsy surgical candidates, with a potential confound of low FSIQ on VSVT performance. The present study replicated the Loring et al. study in a larger sample and extended their findings by examining the relationships among VSVT performance, FSIQ, and working memory. A total of 404 patients with medically intractable epilepsy completed a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
10
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 35 publications
2
10
0
Order By: Relevance
“…Conversely, nonvalid PVT performance could reflect greater disease severity or relate to cognitive factors specific to MS. In addition to Suchy and colleagues' (2012) findings that nonvalid VSVT performance related to earlier symptom onset in MS, studies in other populations have shown associations between VSVT performance and measures of processing speed, working memory, and episodic memory (Loring, Larrabee, Lee, & Meador, 2007;Macciocchi, Seel, Alderson, & Godsall, 2006;Keary et al, 2013), all of which are cognitive functions that are often affected in MS (Chiaravalloti & DeLuca, 2008).…”
Section: Introductionmentioning
confidence: 93%
See 1 more Smart Citation
“…Conversely, nonvalid PVT performance could reflect greater disease severity or relate to cognitive factors specific to MS. In addition to Suchy and colleagues' (2012) findings that nonvalid VSVT performance related to earlier symptom onset in MS, studies in other populations have shown associations between VSVT performance and measures of processing speed, working memory, and episodic memory (Loring, Larrabee, Lee, & Meador, 2007;Macciocchi, Seel, Alderson, & Godsall, 2006;Keary et al, 2013), all of which are cognitive functions that are often affected in MS (Chiaravalloti & DeLuca, 2008).…”
Section: Introductionmentioning
confidence: 93%
“…PVT performance has been well-characterized in select patient groups, including mild traumatic brain injury (mTBI) and presurgical epilepsy patients. Prior studies have shown relatively low rates of PVT failure among presurgical epilepsy patients, and this group is often used to represent individuals without presumed external incentives to underperform on neuropsychological testing (Grote et al, 2000;Loring, Lee, & Meador, 2005;Keary et al, 2013). Conversely, a large proportion of patients with mTBI demonstrate lower than expected performance on neuropsychological testing and reduced scores on PVT measures, which is likely due to relatively higher rates of litigation involvement (Greiffenstein, 2009;Belanger, Curtiss, Demery, Lebowitz, & Vanderploeg, 2005;Binder & Rohling, 1996;Mittenberg, Patton, Canyock, & Condit, 2002;Bianchini, Curtis, & Greve, 2006;Green, Rohling, Lees-Haley, & Allen, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…Instead, clinicians will need to consider the possibility that lower performance … may be due to intellectual or working memory limitations (p. 321), irrespective of SVT findings. These findings point to the limits of hard-and-fast rules of distinguishing valid versus invalid test performance based solely on a SVT cut score without, as Keary et al [ 67 ] state, looking ‘… for convergence of findings’ (p. 321).…”
Section: What Modifies Svt and Neuropsychological Test Performance?mentioning
confidence: 92%
“…In a somewhat similar study, Keary et al [ 67 ] examined patients with intractable epilepsy who were potential candidates for surgery with no know external incentive to malinger. In this cohort they examined three SVT performance findings: Valid (meaning at or above cut-score), Questionable (substantially above chance, but below the SVT cut-point) and Invalid (substantially below the cut point).…”
Section: What Modifies Svt and Neuropsychological Test Performance?mentioning
confidence: 99%
See 1 more Smart Citation